Respuesta :
Answer:
(cxd)(x) = 4x^3 + 18x^2 - 10x
Step-by-step explanation:
We have two functions:
c(x) = 4x – 2
d(x) = x2 + 5x
And we need to find (cxd)(x) which is the multiplication of both functions:
(cxd)(x) = (4x – 2)(x^2 + 5x) = 4x × x^2 + 20x^2 - 2x^2 -10x
= 4x^3 + 18x^2 - 10x
Then: (cxd)(x) = 4x^3 + 18x^2 - 10x
Answer: [tex](c*d)(x)=4x^3+18x^2-10x[/tex]
Step-by-step explanation:
You know that the function [tex]c(x)[/tex] and the function [tex]d(x)[/tex] are:
[tex]c(x) = 4x - 2\\\\d(x) = x^2 + 5x[/tex]
Then, in order to find [tex](c*d)(x)[/tex] you need to multiply the function [tex]c(x)[/tex] by the function [tex]d(x)[/tex]:
[tex](c*d)(x)=(4x - 2)(x^2 + 5x)[/tex]
You must remember the Product of powers property, which states that:
[tex](a^m)(a^n)=a^{(m+n)}[/tex]
Now you can apply Distributive property:
[tex](c*d)(x)=4x^3+20x^2-2x^2-10x[/tex]
Finally, add the like terms. Then:
[tex](c*d)(x)=4x^3+18x^2-10x[/tex]